2019
DOI: 10.1186/s12870-019-2152-9
|View full text |Cite
|
Sign up to set email alerts
|

A whole canopy gas exchange system for the targeted manipulation of grapevine source-sink relations using sub-ambient CO2

Abstract: BackgroundElucidating the effect of source-sink relations on berry composition is of interest for wine grape production as it represents a mechanistic link between yield, photosynthetic capacity and wine quality. However, the specific effects of carbohydrate supply on berry composition are difficult to study in isolation as leaf area or crop adjustments can also change fruit exposure, or lead to compensatory growth or photosynthetic responses. A new experimental system was therefore devised to slow berry sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This might be because of preferential allocation of carbon to sugar accumulation rather than anthocyanin biosynthesis under carbon limitation, as suggested by Bobeica et al (2015). Smith et al (2019) developed a system, however, to directly manipulate whole vine carbon assimilation without affecting canopy size or bunch environment via reduced air CO 2 concentration, finding no impact on the ratio of anthocyanins to sugars during maturation, despite a 50% reduction in maturation rate (Edwards et al 2017). Therefore, the decoupling seen here may be because of a more extreme difference in L/F or be influenced by additional factors, possibly interactively with L/F.…”
Section: Effect Of L/f On Sugar and Anthocyanins At Harvestmentioning
confidence: 99%
“…This might be because of preferential allocation of carbon to sugar accumulation rather than anthocyanin biosynthesis under carbon limitation, as suggested by Bobeica et al (2015). Smith et al (2019) developed a system, however, to directly manipulate whole vine carbon assimilation without affecting canopy size or bunch environment via reduced air CO 2 concentration, finding no impact on the ratio of anthocyanins to sugars during maturation, despite a 50% reduction in maturation rate (Edwards et al 2017). Therefore, the decoupling seen here may be because of a more extreme difference in L/F or be influenced by additional factors, possibly interactively with L/F.…”
Section: Effect Of L/f On Sugar and Anthocyanins At Harvestmentioning
confidence: 99%
“…The sprawling system accumulated a larger concentration of reducing sugars (8%). In other studies, contrary to what has been observed, the minimal modification of the canopy has led to a slowdown in the accumulation of sugars as a consequence of the photosynthetic response of the vine [27]. In this case, the microclimate, besides the CO 2 exchange and the berries' exposure, may have had an impact on the chemical composition of the berries.…”
Section: Chemical Compositionmentioning
confidence: 68%
“…These results are the opposite of other studies, where more reducing sugar with heavy canopy management (12.97%) was obtained. Despite this, differences between the control and canopy management cultivars can be observed [27]. Other statistical differences between trimming trials can be seen in the concentrations of malic acid and tartaric acid.…”
Section: Chemical Compositionmentioning
confidence: 98%
“…Ample withinyear variation of these parameters is not surprising at all. Taking example of TSS vs total anthocyanins behaviour, while both are quite sensitive to crop load, it is well understood that TSS primarily react to whole-canopy photosynthesis (Salazar-Parra et al 2018;Smith et al, 2019), whereas colour accumulation is more heavily impacted by local micro-climate conditions and cultural practices affecting light distribution in the fruiting area and, most importantly, cluster temperature (Haselgrove et al, 2000;Poni et al, 2018). Nonetheless, inter-annual spatial variability in this study was definitely minor regardless of any involved growth, yield or fruit quality parameters.…”
Section: Discussionmentioning
confidence: 99%